Karen's ghost - Yingst, DK; Yingst, DK; Martin, Ann M., 1955- (Baby-sitters little sister (Graphix (Firm)), 2025)
Karen thinks there's a ghost in her house! But she has never really seen the ghost of Old Ben Brewer until now. Karen and her stepsister, Kristy, have found out that Ben Brewer and his spooky friends are going to have a birthday party in their attic on Halloween night! It used to be fun having a ghost around. But now Karen isn't so sure!